2021
DOI: 10.3390/membranes11060453
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Cervical Cancer and HPV Infection

Abstract: Since their description, extracellular vesicles (EVs) have shown growing relevance in cancer progression. These cell structures contain and transfer molecules such as nucleic acids (including DNA and RNA), proteins, and lipids. Despite the rising information about EVs’ relationship with cancer, there is still scarce evidence about their content and function in cervical cancer. Interestingly, the composition and purposes of some cellular molecules and the expression of oncogenic proteins packaged in EVs seem mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Extracellular vesicles (EVs) play important roles in cell-to-cell communication and modulate biological functions by transferring the bioactive molecules (Acevedo-Sánchez et al, 2021;Domenis et al, 2021). In our study, we successfully isolated EVs from SiHa, HeLa, and C-33A cells through classical characterization methods, including TEM and NTA (Kaczmarek et al, 2022;Qadir et al, 2018), and found that MMP-2 showed higher levels in EVs secreted by HPV-positive SiHa and HeLa cells than those in EVs secreted by These results are consistent with the previous findings that MMP-2 is an inducer of cervical cancer (Chatterjee et al, 2003;Lopez-Charcas et al, 2018;Lubowicka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) play important roles in cell-to-cell communication and modulate biological functions by transferring the bioactive molecules (Acevedo-Sánchez et al, 2021;Domenis et al, 2021). In our study, we successfully isolated EVs from SiHa, HeLa, and C-33A cells through classical characterization methods, including TEM and NTA (Kaczmarek et al, 2022;Qadir et al, 2018), and found that MMP-2 showed higher levels in EVs secreted by HPV-positive SiHa and HeLa cells than those in EVs secreted by These results are consistent with the previous findings that MMP-2 is an inducer of cervical cancer (Chatterjee et al, 2003;Lopez-Charcas et al, 2018;Lubowicka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer progression depends on HPV and multiple heterotypic cell interactions that make up the tumor environment. In examining these effects, the potential of using exosomes, which play a role in cellular communication, as a diagnostic and therapeutic biomarker, is being investigated [ 29 , 30 ]. Our study isolated mesenchymal stem cells from umbilical cord tissue wharton jelly and purified the exosomes they secreted out of the cell in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Virus-modified EVs may participate in the remodeling of the cancer microenvironment into proangiogenic and immunosuppressive, promoting cell migration and invasion by transferring oncogenic factors to the adjacent cells [ 63 , 96 ]. Potentially, EVs obtained by a noninvasive method, such as biopsy, might serve as a biomarker of cancer advancement [ 63 , 96 ].…”
Section: The Potential Role Of Extracellular Vesicles As Biomarkers I...mentioning
confidence: 99%